Analisis Kedudukan dan Peran Otoritas Jasa Keuangan (OJK) dalam Pengawasan dan Regulasi Sistem Perbankan Syariah di Indonesia - Khairul Hanif; Muhammad Albahi; Rozi Andrini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study analyzes the position and role of the Financial Services Authority (OJK) in supervising and regulating the Indonesian Islamic banking system. This research uses a descriptive qualitative approach with library research methods. The study examines laws, OJK regulations, and scientific literature on Islamic financial supervision. This analysis highlights the OJK's dual function as a regulator and supervisor in maintaining sharia compliance, financial stability, and governance in Islamic banks. The findings reveal that the OJK holds a strategic position as an independent authority based on Law No. 21 of 2011 and Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector. OJK's on-site and off-site supervision ensures transparency, risk management, and compliance with sharia principles. Challenges include limited human resources with dual expertise, weak harmonization with the National Sharia Council (DSN-MUI), and low public literacy. This study concludes that strengthening the role of the OJK requires increased institutional coordination, capacity building, and integration of maqasid al-shari’ah principles to ensure sustainable development of Islamic finance.